Papua New Guinea food price bulletin: October 2021 - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
Sweet potato and cassava prices in Port Moresby gradually increased in quarter 3, however staple prices in other markets (Lae, Mt. Hagen, Goroka, Kokopo) across the country remained relatively stable . Vitamin-rich food (such as carrots, broccoli, and pawpaw) prices remained relatively stable in quarter 3. Select vegetable and fruit prices increased in Port Moresby.